In-Vitro Evaluation of Antioxidant, Anti-Inflammatory and Anti-Ageing Potentials of Some Common Anti-Ageing Medicinal Plants of Southwest Nigeria (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Ageing is a multifactorial degeneration in body organs and physiological functions. Adansonia digitata linn (AD), Bryophyllum pinnatum (BP), Vernonia amygdalina (VA), and Canna indica (CI) are commonly used in folk medicine as anti-ageing remedies in Southwest Nigeria with little or no scientific bases. This study investigated in-vitro antioxidant, anti-inflammatory, and anti-ageing potentials of these medicinal plants. Ethylacetate Extracts of the powdered leaves of the plants were prepared by cold extraction and were subjected to in-vitro assays: Total Flavonoids content, Hydroxyl radical (OH‑) and 2,2- Diphenyl-1-picrylhydrazyl(DPPH) radical scavenging potentials, Inhibition of lipid peroxidation, Inhibition of Proteinase activity and Protein denaturation, while anti-tyrosinase and Anti-glycation potentials were also evaluated, using standard methods. Results showed that, ethylacetate extract of BP, at 400µg/ml, showed highest Total Flavonoids content Quercetin Equivalent (QE)(1.90mg/g/QE) compared with VA(1.52mg/g/QE), CI(0.80mg/g/QE) and AD(0.4mg/g/QE) respectively and highest OH- radical scavenging potential (66.57%) compared with CI(48.25%), VA(26.53%) and AD(26.43%) respectively. Furthermore, at 400µg/ml, VA exhibited the highest DPPH radical scavenging activity (62.02%) compare with BP(61.98%), AD(53.80%) and CI(45.20%), while AD was more potent at lower concentrations. Moreover, at 400µg/ml, Inhibition of lipid peroxidation was highest in CI(33.07%) compared with AD(26.60%), VA(24.98%), and BP(21.49%), although VA was more potent at lower concentrations. Furthermore, CI exhibited highest proteinase activity inhibition and Inhibition of protein denaturation at concentrations (100 µg/ml - 400µg/ml) while at 400 µg/ml, it elicited highest proteinase inhibition of 94.88% compared with AD(90.50%,), BP(85.89%) and VA(76.1%) respectively and also, highest protein denaturation inhibition of 71.82% compared with BP(59.60%), AD(36.40%) and VA(32.92%) respectively. At the highest concentration of 1mg/ml, VA exhibited the highest anti-tyrosinase activity (IC50 0.28±0.004, 87.28%), while BP, AD, and CI were (IC50 0.32±0.008mg/ml, 77.56%; IC50 0.57±0.009mg/ml, 51.24%; IC50 1.05±0.015mg/ml, 44.35%), respectively. Moreover, across all concentrations (0.3125mg/ml – 5mg/ml) from week 1- 4, VA also, exhibited highest anti-glycation potentials (71.23%, 87.54%, 86.20% and 90.06%) compare with AD(63.30%,75.98%,83.68% and 82.84%), CI (58.75%, 52.62%, 59.94%, and 78.29%) and BP(47.08%, 51.43%, 53.02% and 63.89%) respectively. Vernonia Amygdalina exhibited the highest DPPH radical scavenging, anti-tyrosinase, and anti-glycation properties, while CI showed the highest inhibition of lipid peroxidation, protein denaturation, and proteinase activity. BP exhibited the highest OH- radical scavenging potential and total flavonoids content. The plants may be employed as anti-ageing remedies and also in the management and treatment of other oxidative stress related diseases.